Genome-wide Identification and Evolutionary Analysis of NBS-LRR Genes From Secale cereale - Qian, Lan-Hua; Wang, Yue; Chen, Min; Liu, Jia; Lu, Rui-Sen; Zou, Xin; Sun, Xiao-Qin; Zhang, Yan-Mei (Frontiers in Genetics, 2021)
Secale cereale is an important crop in the Triticeae tribe of the Poaceae family, and it has unique agronomic characteristics and genome properties. It possesses resistance to many diseases and serves as an important resource for the breeding of other Triticeae crops. We performed a genome-wide study on S. cereale to identify the largest group of plant disease resistance (R) genes, the nucleotide binding site-leucine-rich repeat receptor (NBS-LRR) gene. In its genome, 582 NBS-LRR genes were identified, including one from the RNL subclass and 581 from the CNL subclass. The NBS-LRR gene number in the S. cereale genome is greater than that in barley and the diploid wheat genomes. S. cereale chromosome 4 contains the largest number of NBS-LRR genes among the seven chromosomes, which is different from the pattern in barley and the genomes B and D of wheat but similar to that in genome A of wheat. Further synteny analysis suggests that more NBS-LRR genes on chromosome 4 have been inherited from a common ancestor by S. cereale and the wheat genome A than the wheat genomes B and D. Phylogenetic analysis revealed that at least 740 NBS-LRR lineages are present in the common ancestor of S. cereale, H. vulgare and T. urartu. However, most of them have only been inherited by one or two species, with only 65 of them preserved in all three species. The S. cereale genome inherited 382 of these ancestral NBS-LRR lineages, but 120 of them have been lost in both H. vulgare and T. urartu. This study provides the full NBS-LRR profile of the S. cereale genome, which is a resource for S. cereale breeding and indicates that S. cereale can be an important material for the molecular breeding of other Triticeae crops.